2011
DOI: 10.1093/infdis/jir474
|View full text |Cite
|
Sign up to set email alerts
|

Viruslike Particle Vaccine Induces Protection Against Respiratory Syncytial Virus Infection in Mice

Abstract: This study demonstrates that VLP vaccination provides effective protection against RSV infection. VLPs containing RSV-F and/or RSV-G are potential vaccine candidates against RSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
184
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 120 publications
(187 citation statements)
references
References 36 publications
3
184
0
Order By: Relevance
“…[5][6][7][8][9] Compared to FI-RSV, immunization with RSV VLP vaccines induced a higher IgG2a/IgG1 antibody ratio, which refers to Th1 immune responses. 5,6 Nanoparticles of FG VLPs were shown to be in a range of 60-120 nm-size particles and produced in insect cells using the recombinant baculovirus expression system. 5 Alveolar macrophages (AMs) are the first defense line of innate immune cells in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Compared to FI-RSV, immunization with RSV VLP vaccines induced a higher IgG2a/IgG1 antibody ratio, which refers to Th1 immune responses. 5,6 Nanoparticles of FG VLPs were shown to be in a range of 60-120 nm-size particles and produced in insect cells using the recombinant baculovirus expression system. 5 Alveolar macrophages (AMs) are the first defense line of innate immune cells in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nanoparticles of FG VLPs were shown to be in a range of 60-120 nm-size particles and produced in insect cells using the recombinant baculovirus expression system. 5 Alveolar macrophages (AMs) are the first defense line of innate immune cells in the respiratory tract. AMs are a major resident cell in alveoli and interstitial spaces of the lung.…”
Section: Introductionmentioning
confidence: 99%
“…5 In the insect cell expression system, full length RSV F or G proteins were effectively incorporated into VLPs. 10 In cotton rats, this study demonstrated that F VLP was more immunogenic and effective in clearing lung viral titers than G VLP although both F VLP and G VLP did not cause weight loss and AHR lung disease after RSV challenge. FI-RSV immune and na€ ıve cotton rats showed high AHR representing RSV disease mimicking the RSV pathogenesis in humans.…”
Section: Discussionmentioning
confidence: 72%
“…Viral titers in individual lungs at day 5 after challenge were determined using an immune plaque assay as previous described. 10 Lung histopathology and flow cytometry…”
Section: Airway Hyper-responsiveness and Lung Viral Titersmentioning
confidence: 99%
See 1 more Smart Citation